B30 Integrated mitochondrial function in human fine-needle muscle biopsies of huntington's disease mutation carriers and in tissues of HdhQ111 mice. (13th September 2016) - Buck, Eva; Merz, Tamara; Gumpp, Anja; Witting, Anke; Steinacker, Jürgen; Zügel, Martina; Schumann, Uwe; Landwehrmeyer, Bernhard; Weydt, Patrick; Calzia, Enrico; Lindenberg, Katrin S
Abstract : The neurodegenerative genetic disorder of Huntington's disease (HD) is characterised by mitochondrial impairments of the respiratory chain. The ubiquitous expression of the disease causing mutant huntingtin gene raises the question to which extent changes in mitochondrial respiration are evident in the human skeletal muscle. In addition characterisation of mitochondrial respiration in the muscle might allow conclusions about the respiratory status in the brain. The integrated respiratory chain function of the human quadriceps vastus lateralis was measured by high-resolution respirometry in fine-needle biopsies of four pre-symptomatic HD mutation carriers and seven controls. The respiratory parameters indicated a trend towards a reduction in the respiratory control ratio (RCR) of the HD carriers. In parallel, murine cortex, liver, soleus muscle and heart of male HD knock-in mice (Hdh Q111 ), were examined by the same method. Significant changes of the respiration were restricted to the liver and the cortex. In addition mitochondrial DNA copy number and citrate synthase activity were determined to quantify the mitochondrial mass, showing no differences. From the murine tissues mRNA levels of key enzymes characterised the mitochondrial metabolic pathways. We demonstrated the feasibility to perform high-resolution respirometry measurements from small human HD muscle biopsies. Furthermore, we conclude that differences in respiratory parameters of pre-symptomatic human muscle biopsies are rather limited, which is confirmed by the analysis of murine skeletal muscle tissue. The murine cortex and liver turned out to show respiratory changes in the Hdh Q111 mouse model, which indicates that respiratory capacities are different between tissues. Acknowledgement: The work is supported by the research training group cellular and molecular mechanisms in ageing (CEMMA, GRK1789) which is funded by the DFG and the seed fund grant of the EINSTEIN study no 584/14 from the EHDN.